Суммируемость рядов по корневым функциям краевых задач типа Вицадзе - Самарского - Алиев, И.В. (Український математичний журнал, 2008)
Досліджується сумовність за методом Абеля системи власних i приєднаних функцій крайових задач типу Віцадзе - Самарського для еліптичних рівнянь у прямокутнику. Такі задачі зводяться до крайової задачі для еліптичних диференціально-операторних рівнянь з оператором у крайових умовах у відповідних просторах і досліджуються методом диференціально-операторних рівнянь. We investigate the summability of a system of eigenfunctions and associated functions of the Bitsadze –
Samarskii-type boundary-value problems for elliptic equations in a rectangular by the Abel method.
These problems can be reduced to the boundary-value problem for elliptic operator differential equations
with an operator under boundary conditions in the corresponding spaces. We investigate these problems
by the method of operator differential equations.